Curcumin and Cancer: Can It Supplement Chemotherapies for Cancers? - Gholipour, Mahdi; Pouresmaeili, Farkhondeh (Archives of Men's Health, 2020)
Abstract Despite advances in knowledge and information on the causes of cancers, prevention, the excellence of diagnostic systems, and the great achievements of oncology, the incidence of cancer still seems to be on the rise. The used chemical medications, in turn, have shown numerous side effects and cellular toxicity. That is why researchers have always been looking for anti-cancer drugs without adverse effects on the patient. Hence, herbal medicines have received special attention. Curcumin (diferuloylmethane) has been used as a spice in many countries around the world, including Iran, for centuries. Countless properties of this substance, which is obtained from the plant's root, such as anti-inflammatory, anti-mutagenic, anti-cancer, anti-fungal have been reported. This substance is able to affect cell signaling through multiple biochemical pathways, proliferation, differentiation, and cell death. The purpose of writing this review was to examine curcumin and its anti-cancer properties in a general view for its use in practical medicine. Curcumin, with its epigenetic changes in the level of chromatin, is effective in regulating the expression of major and regulatory genes and can play a cancer-preventing role in the cell. Also, this substance and its compounds with inhibition activity of viral protein ACE-2 and Spike glycoprotein of SARS-CoV-2, and regulation of innate immune response have shown several roles in the fight against diseases. To better understand the mechanism of action of turmeric metabolites with stimulant or inhibitory properties, it is necessary to do more research on the particular effects of Curcumin on various diseases, including cancer, effective dose and how to use it alone or in combination with other drugs.